Ectoenzymatic ratios in relation to particulate organic matter distribution (Ross Sea, Antarctica) - MISIC, CRISTINA; POVERO, PAOLO; FABIANO, MAURO (Microbial Ecology, 2002)
The results of a study on ectoenzymatic activity (the enzyme activity bound to particles larger than 0.2 μm) and its relation to organic particle concentration are reported here. The sampling was carried out during the 1994 Antarctic spring, at a fixed station (Station 11) in the polynya of the Ross Sea, an area characterised by quick changes in sea ice cover. The sampling was repeated 4 times over a 20-day time period. The particulate organic matter distribution followed the physical structure of the water column, which depends on ice dynamics and is mainly determined by salinity. In the mixed-water surface layer (0-50 m) the concentrations were higher (on average 65.6 μgC/l), than in the deeper water layer (50 m-bottom), (on average 19.1 μgC/l). This distribution and quality, expressed by the protein:carbohydrate ratio, linked the particulate organic matter to the phytoplanktonic bloom which was in progress in the area. We determined the kinetic parameters of the glycolytic and proteolytic ectoenzymes and also the total activity for the proteolytic enzyme, in order to evaluate the contribution of the particle-bound activity. We observed higher values in the surface layer than in the deeper layer. -glucosidase activity ranged between 0.03 and 0.92 nmol l-1h-1, -N-acetylglucosaminidase activity was in the range of 0.04-0.58 nmol l-1h-1. The total proteolytic activity (leucine aminopeptidase) ranged between 0.85 and 33.71 nmol l-1h-1. The ectoproteolytic activity was about 35% – 60 % of the total. The Km values were slightly higher for the proteolytic activity (on average 0.43 μM for ectoproteolytic activity and 0.58 μM for total proteolytic activity) than for the -glucosidase (on average 0.36 μM) and -N-acetylglucosaminidase (on average 0.17 μM), showing no remarkable variations in the water column. The ectoenzymatic ratios and their relationship with particulate organic substrates confirm the close link between organic substrate availability and degradation system response. The significant and positive ...